2010
DOI: 10.1002/14651858.cd007340.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery for non-alcoholic steatohepatitis in obese patients

Abstract: The lack of randomised clinical trials and quasi-randomised clinical studies precludes us to assess the benefits and harms of bariatric surgery as a therapeutic approach for patients with NASH. Limitations of all other studies with inferior design did not allow us to draw any unbiased conclusion on bariatric surgery for treatment of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
130
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 63 publications
1
130
0
6
Order By: Relevance
“…Two meta-analyses 144,145 evaluated the effect of bariatric surgery on the liver histology in patients with NAFLD. The meta-analysis by Mummadi et al, 144 showed that steatosis, steatohepatitis, and fibrosis appear to improve or completely resolve after bariatric surgery.…”
Section: Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta-analyses 144,145 evaluated the effect of bariatric surgery on the liver histology in patients with NAFLD. The meta-analysis by Mummadi et al, 144 showed that steatosis, steatohepatitis, and fibrosis appear to improve or completely resolve after bariatric surgery.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…The meta-analysis by Mummadi et al, 144 showed that steatosis, steatohepatitis, and fibrosis appear to improve or completely resolve after bariatric surgery. However, a recently published Cochrane review 145 concluded that lack of randomized clinical trials or quasi-randomized clinical studies prevents definitive assessment of benefits and harms of bariatric surgery as a therapeutic approach for patients with NASH.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…A meta-analysis conducted by Mummadi et al, 157 in which the surgical techniques analyzed were mixed, revealed that steatosis, steatohepatitis and fibrosis appeared to improve or become completely resolved in the majority of patients after bariatric surgeryinduced weight loss. These authors emphasized the limitations of their study, regarding mainly the vast heterogeneity of the overall designs and expected outcomes of the studies included.…”
Section: Systematic Reviews and Synthesismentioning
confidence: 99%
“…65,66 In a Cochrane review, four studies showed worsening of fibrosis in patients with NAFLD, mainly in patients with advanced fibrosis, suggesting that the surgery may not be safe in all patients. 67 Considering the risk of worsening of fibrosis, patients undergoing bariatric surgery should be closely monitored.…”
Section: Bariatric Surgerymentioning
confidence: 99%